Role of Helicobacter pylori Eradication in Preventing Gastric Cancer and Reducing Surgical Burden - Adnan ur Rehman, Rutaba Alam, Shazmah, M. Subhan Shahid, Ghulam Murtaza, Sana Ullah Malik, Razwan Ashraf MD (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Helicobacter pylori (H. pylori) is a WHO-classified class I carcinogen and the leading modifiable risk factor for non-cardia gastric cancer. Early eradication interrupts the inflammatory cascade responsible for chronic gastritis, atrophy, intestinal metaplasia, and eventual malignancy. In addition to preventing gastric cancer, successful eradication decreases complications of peptic-ulcer disease, potentially reducing the long-term surgical burden. This study evaluates eradication outcomes among adult patients and analyzes the preventive impact on precancerous gastric pathology. Methods: This descriptive cross-sectional study was conducted at MTI Hayatabad Medical Complex (HMC), Peshawar, and Aziz Bhatti Shaheed Teaching Hospital, Gujrat, Pakistan, from June 2022 to June 2023. A total of 100 adult patients presenting with dyspepsia or suspected H. pylori infection were recruited through non-probability consecutive sampling. Diagnosis was confirmed using urea breath test, stool antigen test, or endoscopic biopsy where indicated. Patients received either bismuth-based quadruple therapy or concomitant therapy. Post-treatment eradication was reassessed after four weeks. Endoscopy with histopathology was performed in symptomatic or clinically indicated cases. Data were analyzed using SPSS version 25, with chi-square and t-tests applied where appropriate. Results: The mean age of participants was 41.8 ± 12.6 years, with males comprising 54% of the sample. Common symptoms included epigastric pain (73%), bloating (52%), and early satiety (38%). The overall eradication success rate was 81%, higher among patients receiving bismuth-based quadruple therapy compared with concomitant therapy. Smoking significantly reduced treatment success (62% vs. 86% in non-smokers). Among 32 patients who underwent endoscopy, chronic active gastritis was found in 68.7%, gastric atrophy in 21.8%, and intestinal metaplasia in 9.3%. Patients with advanced mucosal changes showed lower eradication rates. The findings suggest a clear potential for reducing future gastric cancer incidence and lowering surgical workload through timely eradication. Conclusion: H. pylori eradication is highly effective and represents a central strategy for primary gastric-cancer prevention. Early diagnosis and treatment halt progression toward premalignant lesions and reduce ulcer-related complications, thereby diminishing the need for major upper-gastrointestinal surgeries such as gastrectomy and emergency ulcer repair. Integrating widespread testing, eradication protocols, and patient counseling into routine clinical practice can significantly reduce the long-term surgical burden in high-prevalence regions. Keywords: Helicobacter pylori, gastric cancer prevention, eradication therapy, peptic ulcer, precancerous lesions, surgical burden.